Exhaust Manifold Assessment for Backpressure Minimization - Muhammad Izzat Nor, Ma'arof; Asmar, Ahmed Rana; Lim, Khai Hen; Jeyagopi, Raman; Rishan, Murali; Girma, Tadesse Chala (INTI International University, 2023)
Engine exhaust back pressure is defined as the exhaust gas pressure that is produced by the engine to overcome the hydraulic resistance of the exhaust system to discharge the gases into the atmosphere. Minimizing the level of backpressure will improve the overall performance of the engine as proven by various literature. The aim of this study was to study the effects of manipulating the exhaust manifold’s diameter of a spark ignition (SI) engines with respect to its backpressure. The exhaust manifold’s diameter tested were 46mm, 49mm and 52mm respectively. The bending radius for the manifold was fixed at 50mm. The 3D-model of the exhaust manifolds were developed via Computer Aided Design (CAD) with the use of SolidWork software. Computational Fluid Dynamics (CFD) was then conducted via ANSYS Workbench 2021 R1. The exhaust manifold was designed in reference to the KTM 690 motorcycle. The results showed that the pressure at the bent for the 46mm specification was 270.2Pa, while, the pressure before and at the outlet which was similar at 101.7Pa for both. Identical pattern of data was also obtained for the 49mm exhaust manifold’s diameter, albeit, the pressure at the bent was 194.4Pa and 34.02Pa for pressure at the bent and outlet respectively. Contradicting to these, the 52mm exhaust manifold’s diameter had shown constant pressure reading throughout the manifold at 170.4Pa. From these data, the lowest average backpressure was determined. Thus, the 49mm diameter is found to be optimal with the average backpressure of 87.48Pa throughout the exhaust manifold. This is a novel finding since the effects given by the diameter towards the average backpressure of this specific exhaust is determined. For future studies, assessment on the effects given by the bending radius with respect to the backpressure is recommended to be explored.